Assistive technologies and habit development: a Semiotic Model of Technological Mediation - Sørensen Bent; Thellefsen Martin; Thellefsen Torkild (Language and Semiotic Studies, 2024)
In the field of philosophy of technology, the concept of mediation is central to understanding how technology shapes human experience and behavior. Our aim in this paper is to contribute to the understanding of technological mediation, in particular how and why it is possible. Technological mediation occurs within a mediation space between the technological realm and the user realm. In the technological realm, technology regularizes events and actions, while in the user realm, the user interprets the significative potential of the technology. This interpretation process is identical with use and involves the formation of user habits, which are constrained by technological, cognitive, and sociocultural factors. To provide a theoretical framework for our analysis, we propose the Semiotic Model of Technological Mediation (SMTM), which draws on Charles Peirceʼs semiotics. To illustrate our argument, we focus on assistive technology and provide a recurring example of the Medimi®Smart, a digital, comprehensive system for medication handling.